Implementation of Limited Liability Company Dissolution Reviewed from Law Number 40 of 2007 (Case Study At PT Sumber Berkat Jaya Hidup Baru- Batam City) ". - Ricco Fernando; Benny Djaja (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
To anticipate the possibility of dissolving a PT, the legislators also include a number of provisions regarding conditions that must be met if a PT wants to be dissolved, must follow the dissolution procedure based on statutory provisions. The research method used is normative juridical, normative legal research which consists of a method based on the steps of discovering legal principles, legal systematics, and the level of legal synchronization that is being faced. The implementation of the dissolution of the Limited Liability Company is reviewed from Law Number 40 of 2007 concerning Limited Liability Companies. The dissolution of a Limited Liability Company requires stages according to the provisions of Law Number 40 of 2007 concerning Limited Liability Companies.